Nutrient digestibility of broiler chicken fed diets supplemented with probiotics phytase-producing. Issue 1 (March 2020) - Anggraeni, A S; Suryani, A E; Sofyan, A; Sakti, A A; Istiqomah, L; Karimy, M F; Darma, I N G
Abstract: Phytic acid is an anti-nutrition substance due to its ability to bind minerals such as Mg, Fe, Zn, Mn, Ca, and enzyme proteins resulted in decrease in mineral solubility. Phytic acid levels can be reduced by phytase [myo-inositol hexacryphosphate phosphohidrolase]. Microbial phytase can come from fungi, bacteria, and yeast sources. This research was conducted with the aims to evaluate the effect of probiotics phytase-producing supplementation as feed additive on nutrient digestibility of broiler. This study was performed in a completely randomized design for the environmental design, which consist of five treatments. Negative control (without probiotics phytase-producing), LAB ( Lactobacillus plantarum A1-E) phytase-producing, yeast ( Candida tropicalis TKD-3) phytase-producing, probiotic consortium ( L. plantarum A1-E and C. tropicalis TKD-3) and positive control (commercial probiotic). The observed variables are feed intake, energy intake, excreta weight, energy excretion, nitrogen intake, nitrogen excretion, nitrogen retention, apparent metabolizable energy (AME), true metabolizable energy (TME), apparent metabolizable energy corrected for nitrogen (AMEn) and true metabolizable energy corrected for nitrogen (TMEn). Data were analyzed by using analysis of variance (ANOVA) and followed by Duncan's multiple range test to distinguish the effect of different treatment mean. The results of variation analysis on AMEn and TMEn showed significant different while another parameter showed no significant difference between treatments. The use of C. tropicalis TKD-3 as probiotics phytase-producing on broiler chicken diet increase nutrient digestibility, especially apparent metabolic energy corrected nitrogen, and true metabolic energy corrected nitrogen.